RASA SYUKUR, DUKUNGAN SOSIAL DAN KESEJAHTERAAN GURU DI MASA PANDEMI - Listia Qisthy; Riana Sahrani; Fransisca I. R. Dewi (Jurnal Psikologi, 2023)
During the COVID-19 pandemic, many countries implemented health protocols and implemented lockdowns several times. This causes changes in learning activities, thus requiring special teaching methods. Teachers are required to be creative in conveying material through online (online) learning media. Likewise, teachers and students who initially studied face-to-face are now forced to study from home online. This can cause teachers to feel pressured. Gratitude and social support received (perceived social support) can help teachers overcome the problems they face. This study aims to determine the role of teacher gratitude and teacher perceived social support for teacher subjective well-being during a pandemic. This research was conducted using an electronic questionnaire aimed at 202 teachers who teach at secondary level schools with an age range of 20-46 years. The measurement tools used are the Gratitude Questionnaire Revised-Multidimensional Scale of Perceived Social Support (R-MSPSS), and the Teacher Subjective Well-Being Questionnaire (TSWQ). As a result of the study, gratitude has a significant role in the teacher’s subjective well variable, as well as perceived social support. The role of the PSS dimension in the TSWQ variable is only seen in the family dimension which has a positive and significant value. Perceived social support and gratitude have a positive and significant role in teacher subjective well-being. The higher the value of perceived social support and gratitude, the higher the subjective well-being.